Introduction: Resignifications of Feminism in Contemporary Germany - Hester Baer (Studies in 20th & 21st Century Literature, 2011)
During the past decade, the German-speaking world has witnessed both a new wave of writing by women and a resurgence of interest in and debate about feminism…
Keywords: feminism; German feminism; German-speaking world; debate; literature; contemporary